Muscleblind-like proteins are novel modulators of the tumor-immune microenvironment. - Austin M Gabel; Edie I Crosse; Andrea E Belleville; Simon J Hogg; Siegen A McKellar; Omar Abdel-Wahab; James D Thomas; Robert K Bradley (PLoS ONE, 2025)
Exploiting the immune system to eradicate cancer cells is an area of intense clinical study. However, the mechanisms that shape the tumor-immune microenvironment are incompletely understood. Here, we identify Muscleblind-like (MBNL) proteins as novel modulators of the tumor-immune microenvironment across diverse cancers. We demonstrate that loss of tumor MBNL expression results in an attenuated response to interferon gamma and reduced tumor antigen presentation in melanoma, breast cancer, and colorectal cancer cells. Parallel experiments in a syngeneic mouse melanoma model revealed that MBNL loss reduces tumor cell killing by CD8 + T cells in vitro and facilitates tumor escape from cytotoxic CD8 + T cell infiltration in vivo. Finally, we extended these studies to 29 human cancer types to find that MBNL expression levels are strongly associated with gene expression signatures of T cell tumor infiltration. These insights suggest that MBNL proteins play important roles in shaping the immune landscape across diverse malignancies.